2020
DOI: 10.1089/photob.2019.4771
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy for the Management of Chemotherapy-Induced Peripheral Neuropathy: An Overview

Abstract: Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common side effect of chemotherapy (CT), affecting 68% of patients. Current treatment strategies are based on pharmacological symptom management, but have limited results. Photobiomodulation therapy (PBMT) is a new and emerging therapeutic tool in the supportive care of cancer patients. In this overview, we explore the usability of PBMT for management of CIPN.Objective: To provide a comprehensive overview of management of CIPN with PBMT. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…A prospective, randomized, placebo-controlled study with seven breast cancer patients with a chemotherapy-induced peripheral neuropathy assessed the efficacy of PBM. Based on the study, there seems to be a tendency towards the prevention of chemotherapy-induced peripheral neuropathy with the photobiomodulation therapy [29]. In addition, a randomized, sham-controlled clinical trial on 70 patients showed that the chemotherapy-induced peripheral neuropathy was significantly reduced, there was no significant reduction in the sham group, and that the addition of physiotherapy had no positive income [30].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, randomized, placebo-controlled study with seven breast cancer patients with a chemotherapy-induced peripheral neuropathy assessed the efficacy of PBM. Based on the study, there seems to be a tendency towards the prevention of chemotherapy-induced peripheral neuropathy with the photobiomodulation therapy [29]. In addition, a randomized, sham-controlled clinical trial on 70 patients showed that the chemotherapy-induced peripheral neuropathy was significantly reduced, there was no significant reduction in the sham group, and that the addition of physiotherapy had no positive income [30].…”
Section: Discussionmentioning
confidence: 99%
“…According to an RCT, PBM induced a significant reduction in the modified Total Neuropathy Score (mTNS) in patients with cancer from different etiologies (239). Another prospective, single-arm study with gastrointestinal cancer patients observed a significant reduction in neurotoxicity symptoms after PBM (240,241).…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…Only a limited amount of clinical trials was performed to investigate the use of PBM in patients affected with CIPN [ 29 ]. Argenta et al conducted a randomized controlled trial with 68 patients with self-reported peripheral neuropathy and a history of taxane or platinum-based chemotherapy exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials on PBM and diabetic neuropathy demonstrated beneficial effects [ 22 25 ]. Moreover, one animal study and two clinical trials showed improvement in CIPN symptoms when PBM was applied [ 26 29 ]. However, these studies focused on the therapeutic application of PBM instead of its preventive use.…”
Section: Introductionmentioning
confidence: 99%